Reception Honoring U.S. District Court Judge Robert E. Coyle at Fresno Swim and Racquet Club - Watkins, Howard::::::::: (1982)
Judges Myron D. Crocker, E. Dean Price, and Robert E. Coyle; U.S. Magistrate Alan Christiansen, Fresno County Bar Association President Robert Oliver